2019
DOI: 10.1177/0193945919864429
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Decision-Making in Advanced Parkinson’s Disease: A Mixed Methods Study

Abstract: People with advanced Parkinson’s disease (PD) are living at home being cared for by a family member. Decisions about health care and living preferences are made in a family context. The aims of the study were to (a) examine the types and timing of the decisions being made by dyads (person with Parkinson’s [PWP] and caregiver) in advanced PD; and (b) explore perceived decision quality relative to specific decisions made. A mixed methods design of semi-structured dyad interviews followed by individual completion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…As PD may affect the life not only of the people with the disease, but also for their whole family, education for selfmanagement of the disease for people with PD and their care partners (13,14,17,18,(21)(22)(23)(24)28,30,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(44)(45)(46)48,50,52) , is an essential part of nursing care. On the theme, it was observed that managing the patient-caregiver binomial includes interventions that aim at the coordination of care for the psychosocial effects of illness that can interfere with relationship interactions, with particular emphasis on strengthening caregiver support networks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As PD may affect the life not only of the people with the disease, but also for their whole family, education for selfmanagement of the disease for people with PD and their care partners (13,14,17,18,(21)(22)(23)(24)28,30,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(44)(45)(46)48,50,52) , is an essential part of nursing care. On the theme, it was observed that managing the patient-caregiver binomial includes interventions that aim at the coordination of care for the psychosocial effects of illness that can interfere with relationship interactions, with particular emphasis on strengthening caregiver support networks.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence (13,14,17,18,(21)(22)(23)(24)28,30,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(44)(45)(46)48,50,52) available on self-management education of the disease for people with PD and their care partners involves promoting health for family members and caregivers, providing family education (13,14,24,37,41,44,48,50) and safe sharing space for conversations on sensitive issues ranging from sexual issues of the couple after diagnosis to issues related to palliative care for patients at the end of life (39) .…”
Section: Education For Self-management Of the Disease For People With...mentioning
confidence: 99%
See 1 more Smart Citation